IODIMETRIC SOLID-SPECTROPHOTOMETRIC DETERMINATION OF THIOCYANATE USING POLYURETHANE FOAM AS A SORBENT: UDC 543.432'831 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Methods iodometric solid-spectrophotometric determination of thiocyanate in water with a limit of detection of 3,0 mkg/dm3 was developed. Method involves oxidation of thiocyanate by iodate, following adding to the reaction mixture excess iodide and detection of excess oxidant on the polyurethane foam.
Keywords: thiocyanate, solid phase extraction, polyurethane foam